Frozen in Memory?: Northern Identity in Imagination and Reality. - Laliberte, Jennifer (2011)
Jennifer Laliberte, KIAC School of Visual Arts, Yukon, Canada, at the NRF 6th open Assembly in Hveragerði, Iceland. September 2011.